Experimental and numerical studies on axially restrained cold-formed steel built-up box columns at elevated temperatures. (August 2020) - Yang, Jingjie; Shi, Yu; Wang, Weiyong; Xu, Lei; Al-azzani, Hisham
Abstract: Experimental and numerical studies on the fire resistance of cold-formed steel (CFS) columns with built-up box-shape sections were conducted in this paper. A series of coupon tensile tests were also performed before the fire resistance tests of the columns to obtain the stress–strain relationship of the steel plate from 20 °C to 800 °C. As a benchmark, the load-bearing capacity tests of the columns at ambient temperature were conducted first, and then the fire resistance tests were performed for eight specimens considering different load ratios and axial restraining stiffness. Afterward, numerical models, including heat transfer and structural analyses, were developed to reproduce the fire-resistance behavior of the columns and verified via test results. Finally, parametric analyses were performed to investigate the influence of load ratio, axial restraint, and rotational restraint on the fire-resistance behavior of the columns. Results indicated that the primary failure mode of the specimens was a combination of local and global flexural buckling, which was sensitive to the longitudinally non-uniform temperature field. Moreover, the increase in load ratio and axial restraining stiffness led to a significant decrease in the critical temperature and failure time. Moreover, even a low level of rotational restraint could enhance the fire-resistance behavior of the column. Highlights: Full-scale tests were carried out on restrained cold-formed steel built-up box columns at elevated temperatures. Failure mode and critical temperature were obtained for axially restrained cold-formed steel built-up box columns. Numerical models based on ABAQUS were developed and verified by the tests. Factors influencing fire response of cold-formed steel built-up box columns were studied.